Correlation Between Clinical and Histopathologic Diagnosis of Oral Potentially Malignant Disorder and Oral Squamous Cell Carcinoma - Molook Torabi; Marzieh Karimi Afshar; Hooman Malekpour Afshar; Iman Mohammahzadeh (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine the frequency of oral potentially malignant disorders and Oral Squamous Cell Carcinoma (OSCC) and evaluate the consistency between their clinical and pathological features. Material and Methods: This retrospective study was conducted on records with a diagnosis of oral leukoplakia, oral erythroplakia, erythroleukoplakia, actinic cheilitis, lichen planus, and OSCC in the Pathology Department of Kerman dental school from September 1997 to September 2017. Data were analyzed in SPSS 21 at the significance level of ≤5%. Results: There were 378 cases of oral potentially malignant disorders and 70 cases of OSCC with a mean age of 46.82 ± 15.24 years. Buccal mucosa was the most frequent site, and lichen planus the most common lesion. Females were significantly older than males in leukoplakia and carcinoma in situ lesions. Clinical diagnosis and histopathology were consistent in 69.03% of cases. Conclusion: Clinical and histopathological diagnoses were consistent in 69.03% of records. The highest degree of clinical compliance with histopathology was observed in OSCC. Dentists should pay attention to oral potentially malignant disorders for early diagnosis to prevent their transformation to malignancy.